A case report of response to crizotinib in chemotherapy-refractory metastatic gallbladder cancer with met amplification and acquired resistance resulting from the loss of MET amplification. Issue 3 (30th July 2021) - Sun, Hongna; Li, Xiaofen; Dai, Shuang; Shen, Xudong; Qiu, Meng
Abstract: Gallbladder cancer (GBC) is a highly invasive disease and the most prevalent malignancy of the biliary system. Patients with GBC are commonly diagnosed at a late stage and have an unfavorable prognosis. Palliative chemotherapy has been the standard care for recurrent or metastatic disease in the past decades. Recently, several targeted therapies have been investigated in advanced biliary tract cancer (BTC) including inhibitors of genes or pathways such as FGFR2 fusions or rearrangements, IDH1 mutations, and NTRK gene fusions. Also, several clinical studies involving molecular stratification have been performed in defined patient groups, for example, BRAF V600E and HER2 . Mesenchymal epithelial transition (MET) encodes a tyrosine kinase receptor and its ligand hepatocyte growth factor is a proto-oncogene. Targeting the MET signaling pathway is an effective strategy in numerous cancer types. However, the poor efficacy of MET inhibitors has been demonstrated in several phase II studies, but currently no reports have explained the potential mechanisms of resistance to MET inhibitors in BTC. In this article, we report a case of metastatic GBC with MET amplification that exhibited a rapid response to crizotinib after the failure of two lines of chemotherapy. After the patient had progressed and discontinued crizotinib, cabozantinib was introduced. Analysis of circulating tumor DNA (ctDNA) by next-generation sequencing (NGS) indicated a loss of MET amplification status. To our knowledge, this is the first case study demonstrating the use of NGS in ctDNA to monitor the development of acquired resistance during anti- MET treatment in GBC.